Implementation Of Cooperative Learning Model With React Strategies To Improve Student Mathematical Problem Solving Ability - Sakti Raja Sihite, Muda; Rosdiana Pangaribuan, Lena (International Journal of Educational Research & Social Sciences, 2023)
This research is an experimental study that examines problem posing in an effort to improve the ability of mathematical problem solving of students conducted at SMA Negeri 15 Medan with a sample of class XI as many as two classes taken randomly.The instrument used in this study was a student mathematical problem solving test in the form of multiple choices to determine the ability of students to solve mathematical problems. The results of the study concluded that mathematical problem solving abilities who obtained cooperative models of Jigsaw with REACT's strategy increased better than the mathematical problem solving abilities who obtained conventional learning. Student activities that follow the cooperative model of Jigsaw with REACT's strategy reflect active activities, and student responses to the cooperative model of Jigsaw with REACT's strategy are very good. Based on the results of the study it can be concluded that the application of the cooperative model of Jigsaw with REACT's strategy is effective in improving mathematical problem solving, and student learning activities.